PENGARUH TERPAAN AKUN INSTAGRAM @SAHABAT.KIPKULIAH TERHADAP PEMENUHAN KEBUTUHAN INFORMASI (KIP- KULIAH) PADA FOLLOWERS - Prasetyo Bonifasius; Atori Firdaus (Jurnal Sosial Humaniora dan Pendidikan, 2023)
The This variety of information makes the @sahabat.kipkuliah account a credible and up-to-date source of information for prospective KIP-K students. This phenomenon is very helpful for prospective students who are looking for reliable information about KIP-K, especially for those who face economic limitations. This study aims to determine whether there is an effect of exposure to the Instagram account @sahabat.kipkulialh on fulfilling information needs in followers. The method used in this research is descriptive quantitative. The results showed that the exposure presented by the account had a positive impact on meeting the information needs of its followers, followers of the @sahabat.kipkuliah Instagram account agreed to access, view, and read within a certain period of time giving attention to the @sahabat.kipkuliah Instagram account such as liking, commenting, and even saving posts for future use.